2016
DOI: 10.1177/2054270416649280
|View full text |Cite
|
Sign up to set email alerts
|

What happens when 55% of acute psychiatric beds are closed in six days: an unexpected naturalistic observational study

Abstract: ObjectiveThe sudden closure of 30 out of 54 acute psychiatric beds in Cornwall presented a stressful challenge to staff but also a natural experiment on how a service dealt with this situation. We aimed to evaluate the outcomes of patients needing to leave the closed ward, how bed occupancy rates were affected and the impact on admission rates.DesignA service evaluation of the impact of the ward closure.SettingA comprehensive secondary NHS mental health service in Cornwall serving 550,000 population.Main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Reducing long-stay patients allows for further bed removals, especially considering that inpatient bed capacity and availability generates utilization and coercive treatments. However, there are economic incentives for inadequately long inpatient bed use (39,40,48,57,64,71,78,79,81,83,116).…”
Section: Inpatient Care Has Inappropriately Long Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing long-stay patients allows for further bed removals, especially considering that inpatient bed capacity and availability generates utilization and coercive treatments. However, there are economic incentives for inadequately long inpatient bed use (39,40,48,57,64,71,78,79,81,83,116).…”
Section: Inpatient Care Has Inappropriately Long Durationmentioning
confidence: 99%
“…The transfer of patients from acute to community care allows for treatment in a more adequate setting, which could improve aggressive behavior and reduces stress of patients and careers generated by acute admissions far from home (48,120).…”
Section: Inpatient Services Are Restrictive Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation confirmed our core hypotheses: CRHT referrals and inpatient admissions were lower during the COVID-19 period than during the same period in the two previous years. Earlier research has shown that inpatient admission rates in the NHS can be decreased in the short term to adapt to pressures-especially urgent pressures (5). We speculate that, with the COVID-19 outbreak at the forefront of individuals' concerns, psychiatric patients were more reluctant to seek treatment, following a pattern of behavior seen in other medical fields (6).…”
Section: Discussionmentioning
confidence: 90%